การสังเคราะห์เซนเซอร์ฐานไบฟีนิลสำหรับการตรวจวัด ไซยาไนด์ไอออน - ธนวัฒน์ ศุขการค้า (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
The objective of this project is to design and synthesize molecular sensor copper(II) complex with dipicolylamine derivative and aminophenylboronic acid derivative containing biphenyl as fluorophore for the detection of cyanide ions. Both molecules also have biphenyl group as building block which is synthesized from 3,3′-biphenyldicarboxaldehyde in 72% yield by using Suzuki coupling reaction. Dipicolylamine was synthesized in 77% yield by using aminealdehyde condensation. Blocked boronic was synthesized in 100% yield by using alcohol condensation. All products were characterized by 1H-NMR and mass spectrometry. However, synthesis of dipicolylamine derivative by amine-aldehyde condensation was not successful but a mono-substituted dipicolylamine derivative was obtained. Similarly, the unsuccessful attempt to synthesize aminophenylboronic acid derivative by amine-aldehyde condensation was a result of side reaction with 3-aminophenylboronic acid. Therefore, blocked boronic was used to synthesize the product. It was found that the product occurred as detected by mass spectrometry. However, the product cannot be separated and purified by column chromatography due to acid properties of the silica gel causing decomposition of the product.